2011
DOI: 10.1074/jbc.m111.274423
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Adaptations to Low Temperature as Revealed by Multiple Mutants of Psychrophilic α-Amylase from Antarctic Bacterium

Abstract: Background: Cold-adapted enzymes remain catalytically active at low temperatures. Results: Mutants of a cold-adapted ␣-amylase stabilized by engineered weak interactions and a disulfide bond have lost the kinetic optimization to low temperatures. Conclusion:The disappearance of stabilizing interactions in psychrophilic enzymes increases the dynamics of active site residues at low temperature, leading to a higher activity. Significance: An experimental support to the activity-stability relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…In this context, cold-active enzymes increase their k cat at the expense of an increase in K m (Feller and Gerday, 2003 ). In fact, stepwise single and multiple mutations engineered on a psychrophilic α-amylase to reconstruct the amino acid substitutions found in a mesophilic homolog exhibit a striking correlation of k cat and K m , such that both decrease concomitanly upon increasing the number of mesophilic residues in the cold-adapted enzyme (Cipolla et al, 2011 ). Nevertheless, some enzymes from psychrophilic organisms that operate under subsaturating substrate concentrations within the cytoplasm exhibit a decrease in this kinetic parameter as an evolutionary strategy for cold adaptation (Bentahir et al, 2000 ; Hoyoux et al, 2001 ; Lonhienne et al, 2001 ).…”
Section: Evolutionary and Molecular Mechanisms Of The Cold-adaptationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, cold-active enzymes increase their k cat at the expense of an increase in K m (Feller and Gerday, 2003 ). In fact, stepwise single and multiple mutations engineered on a psychrophilic α-amylase to reconstruct the amino acid substitutions found in a mesophilic homolog exhibit a striking correlation of k cat and K m , such that both decrease concomitanly upon increasing the number of mesophilic residues in the cold-adapted enzyme (Cipolla et al, 2011 ). Nevertheless, some enzymes from psychrophilic organisms that operate under subsaturating substrate concentrations within the cytoplasm exhibit a decrease in this kinetic parameter as an evolutionary strategy for cold adaptation (Bentahir et al, 2000 ; Hoyoux et al, 2001 ; Lonhienne et al, 2001 ).…”
Section: Evolutionary and Molecular Mechanisms Of The Cold-adaptationmentioning
confidence: 99%
“…Psychrophilic and mesophilic alkaline phosphatases are compared to represent changes in the number of insertions and loop extensions, whereas psychrophilic and mesophilic α-amylases are used for visualizing changes in amino acid sequence related to the modification of several properties, listed below each type of amino acid changes. Modified from Helland et al ( 2009 ) and Cipolla et al ( 2011 ).…”
Section: Evolutionary and Molecular Mechanisms Of The Cold-adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, 17 mutants of this enzyme were constructed, each of them bearing an engineered residue forming a weak interaction found in mesophilic α -amylases but absent in the cold-active α -amylase as well as combinations of up to six stabilizing structural factors [114, 189, 234, 273]. It was shown that these engineered interactions improve all the investigated parameters related to protein stability: the compactness, the kinetically driven stability, the thermodynamic stability, the resistance towards chemical denaturation, and the kinetics of unfolding/refolding.Therefore, these mutants of the psychrophilic α -amylase consistently approximate and reproduce the stability and unfolding patterns of the heat-stable enzymes.…”
Section: Activity-flexibility-stability Relationships: Current Issuesmentioning
confidence: 99%
“…These values have to be compared to 295 kcal mol −1 found for the pig pancreatic α-amylase. In a recent work, two multiple mutants of this cold-adapted α- amylase, derived from the data recorded from single mutations, were also investigated [ 47 ]. The first, Mut5, bears five mutations, previously described, that correspond, as stated above, to structural peculiarities existing in the mesophilic pig pancreatic α-amylase: N150D introduces a salt bridge, V196F restores an aromatic interaction, K300R provides a bidentate interaction with the chloride ion, and T232V reinforces a hydrophobic cluster, as well as Q164I.…”
Section: Engineering Cold-adapted Enzymesmentioning
confidence: 99%